Elevated C-Reactive Protein and In-Hospital Mortality in Patients with Decompensated Liver Cirrhosis at a Tertiary Care Hospital, Karachi (Medical Forum Monthly, 2026)
Objective: To determine the frequency of elevated C-reactive protein (CRP) and evaluate its association with inhospital death in patients with decompensated chronic liver disease who present to a tertiary care hospital in Karachi.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Medicine, Dr. Ruth Pfau Civil Hospital, Karachi, over a period of five months from July 2025 to November 2025.Methods: Non-probability consecutive sampling was used to select 150 patients with decompensated chronic hepatic illness, ranging in age from 30 to 70 years. The Child-Pugh classification was used to record clinical anddemographic characteristics as well as assess the condition's severity. Serum CRP levels were measured when the patient arrived and categorised as mild (6–50 mg/L), moderate (51–100 mg/L), severe (>100 mg/L), or normal (<5 mg/L). Patients were observed throughout their hospital stay, and the results of in-hospital death were recorded. SPSS version 24 was used for data analysis. The chi-square test was used to evaluate associations; a p-value of less than 0.05 was considered statistically significant.Results: A total of 114 patients had raised CRP (76.0%). Those with moderate and severe CRP elevation had a significantly higher overall in-hospital death rate of 8.0% (12/150) (p<0.05) than those with normal or moderately elevated CRP. Furthermore, patients in the advanced Child-Pugh class were more likely to have elevated CRP.Conclusion: People with decompensated chronic hepatic disease frequently have elevated CRP, which is strongly linked with higher in-hospital mortality. Because of its affordability and ease of use, CRP may be a useful addition to established prognostic methods in the early risk assessment and treatment of hospitalised patients with decompensated cirrhosis.